Screening Diagnostic System for Chronic Obstructive Pulmonary Diseases - Poreva, Anna; Honcharenko, Oleksandr; Tomashevskyi, Roman; Batachenko, Serhiy; Kulichenko, Viacheslav (Institute of Electrical and Electronics Engineers, 2016)
Preventive screening examinations of the population are one of the most effective ways to prevent COPD today. In this paper the problem of technical support of chronic obstructive pulmonary disease diagnosis is described. Transmit channel data and testing of technical capabilities of NRF24L01-module for implementation in screening diagnostic system are analyzed. The present measurements agree with the following IEEE basic standards: IEEE 802.15 and IEEE 802.15g.
Keywords: auscultation; spirometry; phonospirography complex; wireless data transmission